Watching Doraemon: Dismantling hegemony in a Japanese popular series - Setyaningsih, Wahyu Handayani; Wahidati, Lufi (Diksi, 2023)
This article examines hegemony spread through Japanese popular series, Doraemon. In 2008, the character Doraemon was made the Anime Ambassador and was sent around the world to campaign for Japanese popular culture. This appointment is part of the Japanese government's public diplomacy strategy. Doraemon is then synonymous with the perfect character figure, which has become one of the symbols of the progress of the Japanese state. Hegemony theory is used to dissect how ideology works through characters that have become state icons and are widely accepted with a very positive image. The results of the analysis show that patriarchal hegemony works through the depiction of scary female characters, male superiority, and the role of the media as a means of ideological dissemination. The Doraemon series preserves the patriarchy wrapped in a beautiful dream story of a future with Japan's advanced technology.